Kaedah Tafsir: Muthlaq dan Muqayyad - Nur Ikhlas; Alwizar Alwizar (STIKes Ibnu Sina Ajibarang, 2024)
Qur'anic interpretation is an attempt to understand and explain the meanings contained in God's revelation. In this study, the author discusses the application of two main methods in interpreting the Qur'an, namely the mutlaq method and the muqayyad method. The mutlaq method refers to a more general interpretation that is not bound by a specific context, while the muqayyad method leads to an interpretation that depends on the specific context of a particular verse or situation. This study aims to explain the characteristics of the two methods and how they complement each other in understanding the Qur'anic text as a whole. With this approach, it is hoped that readers can gain a deeper understanding of the dynamics of Qur'anic interpretation in a broader context.